Formulation And Evaluation of Dispersible Tablets From Zingiber officinale - U.Gayke, Amol; D.Thorat, Riddhi; Shinde, Vikas; L. Nikam, Preetam; Patil, Sushil; A. Pawar, Bhagyashri; B.Salunke, Prajkta; R.Pawar, Vikas; P.Pardesi, Karansingh; More, Vikas (Journal of Neonatal Surgery, 2025)
Patients who have trouble swallowing can benefit from an oral dissolving medicine delivery system. Since ancient times, Zingiber officinale has been used medicinally to treat a variety of conditions, including motion sickness, nausea brought on by chemotherapy for cancer, moderate stomach distress, coughing, persistent bronchial issues, low-grade infections of all types, and anorexia. In this research paper, Zingiber officinale acts for antimicrobial activity such as reducing respiratory infection, coughing, sore throat, cold, and bronchial conditions. In order to avoid first-pass metabolism, this study explores the feasibility of creating Zingiber officinale disintegrating tablets that dissolve quickly. The Direct Compression method was used to make the disintegrating tablets. Pre- and post- compressional parameters were assessed for the prepared tablets, such as flow characteristics, hardness, friability, disintegration and dissolution experiments, and accelerated stability studies. To create tablets, the various ingredients—including Lactose Monohydrate, MCC PH-102, Croscarmellose Sodium, Sodium Starch Glycolate, Sodium Saccharin, Magnesium Stearate, Glyceryl Behanate, and Propyl Paraben — were investigated alone and in combination. The formulation with croscarmellose sodium as the super disintegrant (F6) has the shortest wetting and disintegration times of all the formulations. It was discovered that the optimized formulations (F6) had a faster rate of dissolving than the other formulations. F6 was determined to be the most promising DT formulation out of all of them